A Meta-Analysis on the Factors That Best Reduce the Achievement Gap. (July 2015) - Jeynes, William H.
A meta-analyses was undertaken to determine the factors that are most related with reducing the achievement gap. The meta-analysis included 30 studies that examined attempts to bridge the achievement gap between White students on one hand and Black and Latino students on the other. The results indicate that several factors are associated with a reduced achievement gap that could help bridge the gap. A number of these factors go beyond the bounds of the school. These findings suggest that social scientists may need a broad and multidisciplinary approach to the achievement gap, in which they consider a variety of factors can potentially reduce the gap. In addition, the results suggest that social scientist may consider combining educational, psychological, and sociological factors to develop a more comprehensive approach to narrowing the achievement gap. The significance of these results is discussed.